Peran Dinas Pariwisata dalam Meningkatkan Pendapatan Asli Daerah di Provinsi Maluku - Berny Jofrans Metwaan; Selpiah Sappe (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
Regional Original Income is one of the sources of regional financial revenue which is the main capital in carrying out development in the regions. Regional Original Income consists of Regional Taxes, Regional Levies, Proceeds from the Management of Separated Regional Assets, and Other Legitimate Original Regional Revenues. To get the maximum revenue from the original regional income, proper management is needed, therefore the researcher decided to conduct research on the management of one of the original regional income sources with the title